ANALYZING STUDENTS MASTERY OF EXCEL DATA FEATURES IN OFFICE ADMINISTRATION EDUCATION - Intan Fitria Khalila; Marsofiyati; Eka Dwi Utari (International Journal of Teaching and Learning, 2025)
This study aims to analyze the level of mastery among Office Administration Education students regarding various data processing features in Microsoft Excel. In today’s digital workplace, proficiency in Excel is essential, yet many students still struggle with functions beyond the basic level. The problem addressed in this research is the gap between the required digital skills in the professional environment and the actual competencies possessed by students. A descriptive quantitative method was employed, involving five selected students from the 2nd, 4th, and 6th semesters as respondents. Data were collected through a structured Likert-scale questionnaire that measured proficiency across basic, intermediate, and advanced Excel features. The results indicate that students exhibit strong proficiency in basic functions such as SUM and AVERAGE. However, their understanding and application of more complex functions such as IF statements, Pivot Tables, and VLOOKUP are significantly weaker. This suggests a lack of exposure to more advanced digital tools within the current curriculum. The findings underscore the need for more comprehensive and practical digital literacy training to bridge the skills gap and better prepare students for the demands of modern administrative work environments.